Functional Evaluation in High Energy (Schatzker Type V and Type VI) Tibial Plateau Fractures Treated by Open Reduction and Internal Fixation - Khatri, Kavin (Int Sch Res Notices, 2014)
Objective. To review functional outcome in high energy tibial plateau fractures treated by plating. Design. Retrospective analysis. Material and Methods. Sixty-five patients with Schatzker type V and type VI tibial plateau fractures treated with open reduction and internal fixation using plates were included in the study. The functional evaluation of the patients was carried out with Oxford knee scoring. Results. Fifty-four cases (83%) had Oxford knee score between 40 and 48. Seven (10.7%) had score between 30 and 39, three (4.6%) had score between 20 and 29, and one patient (1.5%) had a score of 18. Delayed union was seen in two cases and nonunion was seen in one case. The superficial wound infection was noticed in (9.2%) patients which was resolved with regular dressings and oral antibiotics. Three (4.6%) patients had developed deep wound infection and one among them had developed osteomyelitis. Conclusion. Open reduction and internal fixation in high energy tibial plateau fractures can provide good functional results in appropriately selected cases.